Fabrication of hip and pelvis part for designing acetabular implant by using Fused Deposition Modeling (FDM) machine - Wan Yusoff, Wan Ahmad Yusmawiza; Zakariah, Nur Zawanah; Abdullah, Nurshafika; Ani, Mohd Hanafi; Mohd. Mustafah, Yasir (Trans Tech Publications, Switzerland, 2014)
The purpose of this research is to fabricate the hip and pelvis part for designing the acetabular implant by using Fused Deposition Modeling (FDM) technique. The methodology of this research is begin by converting the 2D image of CT into 3D image through Invesalius 3.0 software. Then the 3D image is converted to .stl format and exported to FDM machine for fabrication purpose. The finish prototype of 3D biomodel replica is evaluated in order to define the problem face by the patient. Also, the dimensional accuracy is measured between 3D replica model and 3D virtual model. Based on the result of 3D biomodel, the ball joint of the femur on the right side is dislocating from its original position because of the fracture occur on acetabular socket. The implant for acetabular fracture is design by using CATIA software and the design must ensure to be fit with the fracture area. Therefore, this study has contributed to medical area especially in Malaysia in improving patient specific preoperative planning and giving better visualization information of the fracture.